Jump to navigation Jump to search

General

Display information for equation id:math.7085.1 on revision:7085

* Page found: Lagrange reversion theorem (eq math.7085.1)

(force rerendering)

Occurrences on the following pages:

Hash: 35aeb816014de5941860d19c3d3fba1f

TeX (original user input):

g(v)=g(x)+\sum_{k=1}^\infty\frac{y^k}{k!}\left(\frac\partial{\partial x}\right)^{k-1}\left(f(x)^kg'(x)\right)

TeX (checked):

g(v)=g(x)+\sum _{k=1}^{\infty }{\frac {y^{k}}{k!}}\left({\frac {\partial }{\partial x}}\right)^{k-1}\left(f(x)^{k}g'(x)\right)

LaTeXML (experimental; uses MathML) rendering

MathML (11.86 KB / 1.778 KB) :

g ( v ) = g ( x ) + k = 1 y k k ! ( x ) k - 1 ( f ( x ) k g ( x ) ) 𝑔 𝑣 𝑔 𝑥 superscript subscript 𝑘 1 superscript 𝑦 𝑘 𝑘 superscript 𝑥 𝑘 1 𝑓 superscript 𝑥 𝑘 superscript 𝑔 𝑥 {\displaystyle g(v)=g(x)+\sum_{{k=1}}^{\infty}{\frac{y^{k}}{k!}}\left({\frac{% \partial}{\partial x}}\right)^{{k-1}}\left(f(x)^{k}g^{\prime}(x)\right)}
<math xmlns="http://www.w3.org/1998/Math/MathML" id="p1.1.m1.1" class="ltx_Math" alttext="{\displaystyle g(v)=g(x)+\sum_{{k=1}}^{\infty}{\frac{y^{k}}{k!}}\left({\frac{%&#10;\partial}{\partial x}}\right)^{{k-1}}\left(f(x)^{k}g^{\prime}(x)\right)}" display="inline">
  <semantics id="p1.1.m1.1a">
    <mrow id="p1.1.m1.1.31" xref="p1.1.m1.1.31.cmml">
      <mrow id="p1.1.m1.1.31.1" xref="p1.1.m1.1.31.1.cmml">
        <mi id="p1.1.m1.1.1" xref="p1.1.m1.1.1.cmml">g</mi>
        <mo id="p1.1.m1.1.31.1.1" xref="p1.1.m1.1.31.1.1.cmml"></mo>
        <mrow id="p1.1.m1.1.31.1.2" xref="p1.1.m1.1.31.1.cmml">
          <mo stretchy="false" id="p1.1.m1.1.2" xref="p1.1.m1.1.31.1.cmml">(</mo>
          <mi id="p1.1.m1.1.3" xref="p1.1.m1.1.3.cmml">v</mi>
          <mo stretchy="false" id="p1.1.m1.1.4" xref="p1.1.m1.1.31.1.cmml">)</mo>
        </mrow>
      </mrow>
      <mo id="p1.1.m1.1.5" xref="p1.1.m1.1.5.cmml">=</mo>
      <mrow id="p1.1.m1.1.31.2" xref="p1.1.m1.1.31.2.cmml">
        <mrow id="p1.1.m1.1.31.2.1" xref="p1.1.m1.1.31.2.1.cmml">
          <mi id="p1.1.m1.1.6" xref="p1.1.m1.1.6.cmml">g</mi>
          <mo id="p1.1.m1.1.31.2.1.1" xref="p1.1.m1.1.31.2.1.1.cmml"></mo>
          <mrow id="p1.1.m1.1.31.2.1.2" xref="p1.1.m1.1.31.2.1.cmml">
            <mo stretchy="false" id="p1.1.m1.1.7" xref="p1.1.m1.1.31.2.1.cmml">(</mo>
            <mi id="p1.1.m1.1.8" xref="p1.1.m1.1.8.cmml">x</mi>
            <mo stretchy="false" id="p1.1.m1.1.9" xref="p1.1.m1.1.31.2.1.cmml">)</mo>
          </mrow>
        </mrow>
        <mo id="p1.1.m1.1.10" xref="p1.1.m1.1.10.cmml">+</mo>
        <mrow id="p1.1.m1.1.31.2.2" xref="p1.1.m1.1.31.2.2.cmml">
          <mstyle displaystyle="true" id="p1.1.m1.1.31.2.2.1" xref="p1.1.m1.1.31.2.2.1.cmml">
            <munderover id="p1.1.m1.1.31.2.2.1a" xref="p1.1.m1.1.31.2.2.1.cmml">
              <mo largeop="true" movablelimits="false" symmetric="true" id="p1.1.m1.1.11" xref="p1.1.m1.1.11.cmml"></mo>
              <mrow id="p1.1.m1.1.12.1" xref="p1.1.m1.1.12.1.cmml">
                <mi id="p1.1.m1.1.12.1.1" xref="p1.1.m1.1.12.1.1.cmml">k</mi>
                <mo id="p1.1.m1.1.12.1.2" xref="p1.1.m1.1.12.1.2.cmml">=</mo>
                <mn id="p1.1.m1.1.12.1.3" xref="p1.1.m1.1.12.1.3.cmml">1</mn>
              </mrow>
              <mi mathvariant="normal" id="p1.1.m1.1.13.1" xref="p1.1.m1.1.13.1.cmml"></mi>
            </munderover>
          </mstyle>
          <mrow id="p1.1.m1.1.31.2.2.2" xref="p1.1.m1.1.31.2.2.2.cmml">
            <mstyle displaystyle="true" id="p1.1.m1.1.14" xref="p1.1.m1.1.14.cmml">
              <mfrac id="p1.1.m1.1.14a" xref="p1.1.m1.1.14.cmml">
                <msup id="p1.1.m1.1.14.2" xref="p1.1.m1.1.14.2.cmml">
                  <mi id="p1.1.m1.1.14.2.1" xref="p1.1.m1.1.14.2.1.cmml">y</mi>
                  <mi id="p1.1.m1.1.14.2.2.1" xref="p1.1.m1.1.14.2.2.1.cmml">k</mi>
                </msup>
                <mrow id="p1.1.m1.1.14.3" xref="p1.1.m1.1.14.3.cmml">
                  <mi id="p1.1.m1.1.14.3.1" xref="p1.1.m1.1.14.3.1.cmml">k</mi>
                  <mo lspace="0pt" rspace="3.5pt" id="p1.1.m1.1.14.3.2" xref="p1.1.m1.1.14.3.2.cmml">!</mo>
                </mrow>
              </mfrac>
            </mstyle>
            <mo id="p1.1.m1.1.31.2.2.2.1" xref="p1.1.m1.1.31.2.2.2.1.cmml"></mo>
            <msup id="p1.1.m1.1.31.2.2.2.2" xref="p1.1.m1.1.31.2.2.2.2.cmml">
              <mrow id="p1.1.m1.1.31.2.2.2.2.2" xref="p1.1.m1.1.16.cmml">
                <mo id="p1.1.m1.1.15" xref="p1.1.m1.1.16.cmml">(</mo>
                <mstyle displaystyle="true" id="p1.1.m1.1.16" xref="p1.1.m1.1.16.cmml">
                  <mfrac id="p1.1.m1.1.16a" xref="p1.1.m1.1.16.cmml">
                    <mo id="p1.1.m1.1.16.2" xref="p1.1.m1.1.16.2.cmml"></mo>
                    <mrow id="p1.1.m1.1.16.3" xref="p1.1.m1.1.16.3.cmml">
                      <mo id="p1.1.m1.1.16.3.1" xref="p1.1.m1.1.16.3.1.cmml"></mo>
                      <mo id="p1.1.m1.1.16.3a" xref="p1.1.m1.1.16.3.cmml"></mo>
                      <mi id="p1.1.m1.1.16.3.2" xref="p1.1.m1.1.16.3.2.cmml">x</mi>
                    </mrow>
                  </mfrac>
                </mstyle>
                <mo id="p1.1.m1.1.17" xref="p1.1.m1.1.16.cmml">)</mo>
              </mrow>
              <mrow id="p1.1.m1.1.18.1" xref="p1.1.m1.1.18.1.cmml">
                <mi id="p1.1.m1.1.18.1.1" xref="p1.1.m1.1.18.1.1.cmml">k</mi>
                <mo id="p1.1.m1.1.18.1.2" xref="p1.1.m1.1.18.1.2.cmml">-</mo>
                <mn id="p1.1.m1.1.18.1.3" xref="p1.1.m1.1.18.1.3.cmml">1</mn>
              </mrow>
            </msup>
            <mo id="p1.1.m1.1.31.2.2.2.1a" xref="p1.1.m1.1.31.2.2.2.1.cmml"></mo>
            <mrow id="p1.1.m1.1.31.2.2.2.3" xref="p1.1.m1.1.31.2.2.2.3.2.cmml">
              <mo id="p1.1.m1.1.19" xref="p1.1.m1.1.31.2.2.2.3.2.cmml">(</mo>
              <mrow id="p1.1.m1.1.31.2.2.2.3.2" xref="p1.1.m1.1.31.2.2.2.3.2.cmml">
                <mi id="p1.1.m1.1.20" xref="p1.1.m1.1.20.cmml">f</mi>
                <mo id="p1.1.m1.1.31.2.2.2.3.2.1" xref="p1.1.m1.1.31.2.2.2.3.2.1.cmml"></mo>
                <msup id="p1.1.m1.1.31.2.2.2.3.2.2" xref="p1.1.m1.1.31.2.2.2.3.2.2.cmml">
                  <mrow id="p1.1.m1.1.31.2.2.2.3.2.2.2" xref="p1.1.m1.1.31.2.2.2.3.2.2.cmml">
                    <mo stretchy="false" id="p1.1.m1.1.21" xref="p1.1.m1.1.31.2.2.2.3.2.2.cmml">(</mo>
                    <mi id="p1.1.m1.1.22" xref="p1.1.m1.1.22.cmml">x</mi>
                    <mo stretchy="false" id="p1.1.m1.1.23" xref="p1.1.m1.1.31.2.2.2.3.2.2.cmml">)</mo>
                  </mrow>
                  <mi id="p1.1.m1.1.24.1" xref="p1.1.m1.1.24.1.cmml">k</mi>
                </msup>
                <mo id="p1.1.m1.1.31.2.2.2.3.2.1a" xref="p1.1.m1.1.31.2.2.2.3.2.1.cmml"></mo>
                <msup id="p1.1.m1.1.31.2.2.2.3.2.3" xref="p1.1.m1.1.31.2.2.2.3.2.3.cmml">
                  <mi id="p1.1.m1.1.25" xref="p1.1.m1.1.25.cmml">g</mi>
                  <mo id="p1.1.m1.1.26.1" xref="p1.1.m1.1.26.1.cmml"></mo>
                </msup>
                <mo id="p1.1.m1.1.31.2.2.2.3.2.1b" xref="p1.1.m1.1.31.2.2.2.3.2.1.cmml"></mo>
                <mrow id="p1.1.m1.1.31.2.2.2.3.2.4" xref="p1.1.m1.1.31.2.2.2.3.2.cmml">
                  <mo stretchy="false" id="p1.1.m1.1.27" xref="p1.1.m1.1.31.2.2.2.3.2.cmml">(</mo>
                  <mi id="p1.1.m1.1.28" xref="p1.1.m1.1.28.cmml">x</mi>
                  <mo stretchy="false" id="p1.1.m1.1.29" xref="p1.1.m1.1.31.2.2.2.3.2.cmml">)</mo>
                </mrow>
              </mrow>
              <mo id="p1.1.m1.1.30" xref="p1.1.m1.1.31.2.2.2.3.2.cmml">)</mo>
            </mrow>
          </mrow>
        </mrow>
      </mrow>
    </mrow>
    <annotation-xml encoding="MathML-Content" id="p1.1.m1.1b">
      <apply id="p1.1.m1.1.31.cmml" xref="p1.1.m1.1.31">
        <eq id="p1.1.m1.1.5.cmml" xref="p1.1.m1.1.5"/>
        <apply id="p1.1.m1.1.31.1.cmml" xref="p1.1.m1.1.31.1">
          <times id="p1.1.m1.1.31.1.1.cmml" xref="p1.1.m1.1.31.1.1"/>
          <ci id="p1.1.m1.1.1.cmml" xref="p1.1.m1.1.1">𝑔</ci>
          <ci id="p1.1.m1.1.3.cmml" xref="p1.1.m1.1.3">𝑣</ci>
        </apply>
        <apply id="p1.1.m1.1.31.2.cmml" xref="p1.1.m1.1.31.2">
          <plus id="p1.1.m1.1.10.cmml" xref="p1.1.m1.1.10"/>
          <apply id="p1.1.m1.1.31.2.1.cmml" xref="p1.1.m1.1.31.2.1">
            <times id="p1.1.m1.1.31.2.1.1.cmml" xref="p1.1.m1.1.31.2.1.1"/>
            <ci id="p1.1.m1.1.6.cmml" xref="p1.1.m1.1.6">𝑔</ci>
            <ci id="p1.1.m1.1.8.cmml" xref="p1.1.m1.1.8">𝑥</ci>
          </apply>
          <apply id="p1.1.m1.1.31.2.2.cmml" xref="p1.1.m1.1.31.2.2">
            <apply id="p1.1.m1.1.31.2.2.1.cmml" xref="p1.1.m1.1.31.2.2.1">
              <csymbol cd="ambiguous" id="p1.1.m1.1.31.2.2.1.1.cmml" xref="p1.1.m1.1.31.2.2.1">superscript</csymbol>
              <apply id="p1.1.m1.1.31.2.2.1.2.cmml" xref="p1.1.m1.1.31.2.2.1">
                <csymbol cd="ambiguous" id="p1.1.m1.1.31.2.2.1.2.1.cmml" xref="p1.1.m1.1.31.2.2.1">subscript</csymbol>
                <sum id="p1.1.m1.1.11.cmml" xref="p1.1.m1.1.11"/>
                <apply id="p1.1.m1.1.12.1.cmml" xref="p1.1.m1.1.12.1">
                  <eq id="p1.1.m1.1.12.1.2.cmml" xref="p1.1.m1.1.12.1.2"/>
                  <ci id="p1.1.m1.1.12.1.1.cmml" xref="p1.1.m1.1.12.1.1">𝑘</ci>
                  <cn type="integer" id="p1.1.m1.1.12.1.3.cmml" xref="p1.1.m1.1.12.1.3">1</cn>
                </apply>
              </apply>
              <infinity id="p1.1.m1.1.13.1.cmml" xref="p1.1.m1.1.13.1"/>
            </apply>
            <apply id="p1.1.m1.1.31.2.2.2.cmml" xref="p1.1.m1.1.31.2.2.2">
              <times id="p1.1.m1.1.31.2.2.2.1.cmml" xref="p1.1.m1.1.31.2.2.2.1"/>
              <apply id="p1.1.m1.1.14.cmml" xref="p1.1.m1.1.14">
                <divide id="p1.1.m1.1.14.1.cmml" xref="p1.1.m1.1.14"/>
                <apply id="p1.1.m1.1.14.2.cmml" xref="p1.1.m1.1.14.2">
                  <csymbol cd="ambiguous" id="p1.1.m1.1.14.2.3.cmml" xref="p1.1.m1.1.14.2">superscript</csymbol>
                  <ci id="p1.1.m1.1.14.2.1.cmml" xref="p1.1.m1.1.14.2.1">𝑦</ci>
                  <ci id="p1.1.m1.1.14.2.2.1.cmml" xref="p1.1.m1.1.14.2.2.1">𝑘</ci>
                </apply>
                <apply id="p1.1.m1.1.14.3.cmml" xref="p1.1.m1.1.14.3">
                  <factorial id="p1.1.m1.1.14.3.2.cmml" xref="p1.1.m1.1.14.3.2"/>
                  <ci id="p1.1.m1.1.14.3.1.cmml" xref="p1.1.m1.1.14.3.1">𝑘</ci>
                </apply>
              </apply>
              <apply id="p1.1.m1.1.31.2.2.2.2.cmml" xref="p1.1.m1.1.31.2.2.2.2">
                <csymbol cd="ambiguous" id="p1.1.m1.1.31.2.2.2.2.1.cmml" xref="p1.1.m1.1.31.2.2.2.2">superscript</csymbol>
                <apply id="p1.1.m1.1.16.cmml" xref="p1.1.m1.1.31.2.2.2.2.2">
                  <divide id="p1.1.m1.1.16.1.cmml" xref="p1.1.m1.1.31.2.2.2.2.2"/>
                  <partialdiff id="p1.1.m1.1.16.2.cmml" xref="p1.1.m1.1.16.2"/>
                  <apply id="p1.1.m1.1.16.3.cmml" xref="p1.1.m1.1.16.3">
                    <partialdiff id="p1.1.m1.1.16.3.1.cmml" xref="p1.1.m1.1.16.3.1"/>
                    <ci id="p1.1.m1.1.16.3.2.cmml" xref="p1.1.m1.1.16.3.2">𝑥</ci>
                  </apply>
                </apply>
                <apply id="p1.1.m1.1.18.1.cmml" xref="p1.1.m1.1.18.1">
                  <minus id="p1.1.m1.1.18.1.2.cmml" xref="p1.1.m1.1.18.1.2"/>
                  <ci id="p1.1.m1.1.18.1.1.cmml" xref="p1.1.m1.1.18.1.1">𝑘</ci>
                  <cn type="integer" id="p1.1.m1.1.18.1.3.cmml" xref="p1.1.m1.1.18.1.3">1</cn>
                </apply>
              </apply>
              <apply id="p1.1.m1.1.31.2.2.2.3.2.cmml" xref="p1.1.m1.1.31.2.2.2.3">
                <times id="p1.1.m1.1.31.2.2.2.3.2.1.cmml" xref="p1.1.m1.1.31.2.2.2.3.2.1"/>
                <ci id="p1.1.m1.1.20.cmml" xref="p1.1.m1.1.20">𝑓</ci>
                <apply id="p1.1.m1.1.31.2.2.2.3.2.2.cmml" xref="p1.1.m1.1.31.2.2.2.3.2.2">
                  <csymbol cd="ambiguous" id="p1.1.m1.1.31.2.2.2.3.2.2.1.cmml" xref="p1.1.m1.1.31.2.2.2.3.2.2">superscript</csymbol>
                  <ci id="p1.1.m1.1.22.cmml" xref="p1.1.m1.1.22">𝑥</ci>
                  <ci id="p1.1.m1.1.24.1.cmml" xref="p1.1.m1.1.24.1">𝑘</ci>
                </apply>
                <apply id="p1.1.m1.1.31.2.2.2.3.2.3.cmml" xref="p1.1.m1.1.31.2.2.2.3.2.3">
                  <csymbol cd="ambiguous" id="p1.1.m1.1.31.2.2.2.3.2.3.1.cmml" xref="p1.1.m1.1.31.2.2.2.3.2.3">superscript</csymbol>
                  <ci id="p1.1.m1.1.25.cmml" xref="p1.1.m1.1.25">𝑔</ci>
                  <ci id="p1.1.m1.1.26.1.cmml" xref="p1.1.m1.1.26.1"></ci>
                </apply>
                <ci id="p1.1.m1.1.28.cmml" xref="p1.1.m1.1.28">𝑥</ci>
              </apply>
            </apply>
          </apply>
        </apply>
      </apply>
    </annotation-xml>
    <annotation encoding="application/x-tex" id="p1.1.m1.1c">{\displaystyle g(v)=g(x)+\sum_{{k=1}}^{\infty}{\frac{y^{k}}{k!}}\left({\frac{%
\partial}{\partial x}}\right)^{{k-1}}\left(f(x)^{k}g^{\prime}(x)\right)}</annotation>
  </semantics>
</math>

SVG (17.276 KB / 5.559 KB) :

g times left-parenthesis v right-parenthesis equals g times left-parenthesis x right-parenthesis plus sigma-summation Underscript k equals 1 Overscript normal infinity Endscripts StartFraction y Superscript k Baseline Over k factorial EndFraction times left-parenthesis StartFraction partial-differential Over partial-differential x EndFraction right-parenthesis Superscript k minus 1 Baseline times left-parenthesis f times left-parenthesis x right-parenthesis Superscript k Baseline times g prime times left-parenthesis x right-parenthesis right-parenthesis

SVG with PNG fallback (MathML can be enabled via browser plugin) rendering

MathML (2.585 KB / 622 B) :

g ( v ) = g ( x ) + k = 1 y k k ! ( x ) k 1 ( f ( x ) k g ( x ) ) {\displaystyle g(v)=g(x)+\sum _{k=1}^{\infty }{\frac {y^{k}}{k!}}\left({\frac {\partial }{\partial x}}\right)^{k-1}\left(f(x)^{k}g'(x)\right)}
<math xmlns="http://www.w3.org/1998/Math/MathML" display="block" alttext="{\displaystyle g(v)=g(x)+\sum _{k=1}^{\infty }{\frac {y^{k}}{k!}}\left({\frac {\partial }{\partial x}}\right)^{k-1}\left(f(x)^{k}g'(x)\right)}">
  <semantics>
    <mrow class="MJX-TeXAtom-ORD">
      <mstyle displaystyle="true" scriptlevel="0">
        <mi>g</mi>
        <mo stretchy="false">(</mo>
        <mi>v</mi>
        <mo stretchy="false">)</mo>
        <mo>=</mo>
        <mi>g</mi>
        <mo stretchy="false">(</mo>
        <mi>x</mi>
        <mo stretchy="false">)</mo>
        <mo>+</mo>
        <munderover>
          <mo>&#x2211;<!-- ∑ --></mo>
          <mrow class="MJX-TeXAtom-ORD">
            <mi>k</mi>
            <mo>=</mo>
            <mn>1</mn>
          </mrow>
          <mrow class="MJX-TeXAtom-ORD">
            <mi mathvariant="normal">&#x221E;<!-- ∞ --></mi>
          </mrow>
        </munderover>
        <mrow class="MJX-TeXAtom-ORD">
          <mfrac>
            <msup>
              <mi>y</mi>
              <mrow class="MJX-TeXAtom-ORD">
                <mi>k</mi>
              </mrow>
            </msup>
            <mrow>
              <mi>k</mi>
              <mo>!</mo>
            </mrow>
          </mfrac>
        </mrow>
        <msup>
          <mrow>
            <mo>(</mo>
            <mrow class="MJX-TeXAtom-ORD">
              <mfrac>
                <mi mathvariant="normal">&#x2202;<!-- ∂ --></mi>
                <mrow>
                  <mi mathvariant="normal">&#x2202;<!-- ∂ --></mi>
                  <mi>x</mi>
                </mrow>
              </mfrac>
            </mrow>
            <mo>)</mo>
          </mrow>
          <mrow class="MJX-TeXAtom-ORD">
            <mi>k</mi>
            <mo>&#x2212;<!-- − --></mo>
            <mn>1</mn>
          </mrow>
        </msup>
        <mrow>
          <mo>(</mo>
          <mrow>
            <mi>f</mi>
            <mo stretchy="false">(</mo>
            <mi>x</mi>
            <msup>
              <mo stretchy="false">)</mo>
              <mrow class="MJX-TeXAtom-ORD">
                <mi>k</mi>
              </mrow>
            </msup>
            <msup>
              <mi>g</mi>
              <mo>&#x2032;</mo>
            </msup>
            <mo stretchy="false">(</mo>
            <mi>x</mi>
            <mo stretchy="false">)</mo>
          </mrow>
          <mo>)</mo>
        </mrow>
      </mstyle>
    </mrow>
    <annotation encoding="application/x-tex">{\displaystyle g(v)=g(x)+\sum _{k=1}^{\infty }{\frac {y^{k}}{k!}}\left({\frac {\partial }{\partial x}}\right)^{k-1}\left(f(x)^{k}g'(x)\right)}</annotation>
  </semantics>
</math>

SVG (12.5 KB / 4.92 KB) :

{\displaystyle g(v)=g(x)+\sum _{k=1}^{\infty }{\frac {y^{k}}{k!}}\left({\frac {\partial }{\partial x}}\right)^{k-1}\left(f(x)^{k}g'(x)\right)}

Translations to Computer Algebra Systems

Translation to Maple

In Maple:

Translation to Mathematica

In Mathematica:

Similar pages

Calculated based on the variables occurring on the entire Lagrange reversion theorem page

Identifiers

MathML observations

0results

0results

no statistics present please run the maintenance script ExtractFeatures.php

0 results

0 results